Formulasi dan Uji Stabilitas Sediaan Deodorant Stick dari Ekstrak Kulit Jeruk Nipis (Citrus aurantifolia) - Almira Rahma Aulia; Indah Jenny Pratiwi; Ratnaningsih Dewi Astuti; Muhamad Taswin (JPP JURNAL KESEHATAN POLTEKKES PALEMBANG, 2025)
Background: Body odor is a problem that is often complained of by almost everyone, especially individuals who live in tropical areas. This problem is caused by the activity of commensal skin bacteria that decompose odorless compounds from sweat into volatile components that cause unpleasant odors. This study is an experimental study to make a deodorant stick preparation from lime peel (Citrus aurantifolia) as an anti-odor drug that can inhibit Staphylococcus epidermidis bacteria. This study aims to develop and evaluate a deodorant stick preparation made from lime peel extract (Citrus aurantifolia) with stearic acid and NaOH as hardening agents. Its physical stability was tested by reviewing organoleptic (changes in color, shape and odor), homogeneity, pH test, melting point, adhesion test and irritation test of the preparation. Methods: This type of research is an experimental study, namely formulating a deodorant stick from lime peel extract (Citrus aurantifolia) with variations of stearic acid and 10% NaOH as a hardening agent and testing its physical stability. Variations in stearic acid concentrations in formula I (5%), formula II (7.5%), and formula III (10%), while for variations in 10% NAOH concentration in formula I (7.2%), formula II (8.5%), and formula III (10%). The deodorant stick that has been made will be tested for its physical stability reviewed from organoleptic (changes in color, shape and odor), homogeneity, pH test, melting point, adhesion test and irritation test of the preparation. Results: Lime peel (Citrus aurantifolia) extract deodorant stick meets the physical test stability requirements which include organoleptic tests, homogeneity, melting point, adhesion, skin irritation and pH tests for 28 days of storage. Conclusion: Based on the results of the study of the physical stability of deodorant sticks from lime peel extract with varying concentrations of stearic acid and NaOH as hardening agents which have been tested for physical stability for 28 days of storage at room temperature and 12 days in an accelerated test (cycling test), reviewed from pH, adhesive power, homogeneity, spreadability, melting point, color, odor and skin irritation, it can be concluded that lime peel extract (Citrus aurantifolia) can be formulated into a deodorant stick preparation that is physically stable and meets the requirements.